2010
DOI: 10.1108/00070701011067497
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing organic food purchase in India – expert survey insights

Abstract: PurposeThe paper aims to document the findings of an expert survey in the organic food category in India. It seeks to highlight the relative importance attached by the experts to key explanatory variables in the consumers' purchase process of organic food. It attempts to integrate with the relevant consumer survey findings published in India in recent times in organic food category.Design/methodology/approachThe list of experts was prepared by including regular and well‐known speakers in different agri enclave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 40 publications
6
76
0
4
Order By: Relevance
“…For instance, prior studies show that the reputation of both the organic food store and organic food are significantly affected by specific consumer opinion leadership and word of mouth (WOM). This reputation influences organic food purchases (Chakrabarti, 2010). These variables may have an effect on building retailer trust and reducing risk.…”
Section: Consumer Response To Retail Performancementioning
confidence: 99%
“…For instance, prior studies show that the reputation of both the organic food store and organic food are significantly affected by specific consumer opinion leadership and word of mouth (WOM). This reputation influences organic food purchases (Chakrabarti, 2010). These variables may have an effect on building retailer trust and reducing risk.…”
Section: Consumer Response To Retail Performancementioning
confidence: 99%
“…The way sustainable consumerism is found gradually moving to Asian countries (Lee, 2014;Gurau and Ranchhod, 2005), India, which is a large emerging economy is found to be a potential market of sustainable brands as well (Singh, 2013). The studies in Indian context, so far, have focused on profiling green consumers and researching on determinants of consumer purchase behaviour for products such as organic food and genetically modified food (Anand, 2011;Chakrabarti, 2010;Knight and Paradkar, 2008). Previous research evidenced that Indian consumers are considering environmental and social factors while making purchase decisions (Singh, Saeed, and Bertsch, 2012;Manaktola and Jauhari, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Given such a role, OL has been studied in marketing for many years (Flynn, Goldsmith, & Eastman, 1996;King & Summers, 1970). In a recent review of literature based on 101 CI studies (Kaushik & Rahman, 2014), OL has been reported as one of the key correlates of innovativeness constructs as it has a direct positive correlation with both domain-specific innovativeness (DSI; Chakrabarti, 2010;Girardi et al, 2005;Goldsmith, Kim, Flynn, & Kim, 2005) and innovativeness behavior (IB; Girardi et al, 2005;Ruvio & Shoham, 2007;Summers, 1971). Hence, the following hypothesis is proposed: Innovativeness has also been defined as "the degree to which an individual makes innovation decisions independently of the communicated experience of others" (Midgley, 1977, p. 49).…”
Section: Hypothesis Developmentmentioning
confidence: 99%